The relationship between liver pathological inflammation degree and pyroptosis in chronic hepatitis B patients. Issue 11 (6th June 2021) - Wang, Yao; Li, Xun; Chen, Qian; Jiao, Fangzhou; Shi, Chunxia; Pei,, Maohua; Wang, Luwen; Gong, Zuojiong
Abstract: The aim of this study is to explore the relationship between liver pathological inflammation degree and pyroptosis in patients with chronic hepatitis B (CHB). One hundred and twenty CHB patients' liver tissue samples, including A0–A3 inflammatory grades, were selected. Six tissue sections were selected for each indicator in each inflammation grade. The results of immunohistochemical analysis on the pyroptosis‐related molecules (NLRP3, GSDMD, caspase1, interleukin [IL]‐1β, and IL‐18) were determined. The correlation between the pyroptosis‐related molecules and liver inflammatory activities was analyzed. The expression of NLRP3, GSDMD, caspase1, IL‐18, and IL‐1β was respectively significantly positively correlated with the grade of inflammatory activity ( r s = 0.690, p < 0.01; r s = 0.681, p < 0.01; r s = 0.540, p < 0.01; r s = 0.725, p < 0.01; r s = 0.663, p < 0.01) and linear relationship ( χ 2 = 56.763, p < 0.01; χ 2 = 55.350, p < 0.01; χ 2 = 34.776, p < 0.01; χ 2 = 62.523, p < 0.01; χ 2 = 52.521, p < 0.01) in liver tissue. The high expression of NLRP3, GSDMD, caspase1, IL‐1β, and IL‐18 may be involved in the process of liver tissue inflammation and damage, which is positively correlated with liver tissue inflammation in patients with CHB. Highlights: It illustrates a significant mechanistic finding given the fact that with the aggravation of liver inflammation, the expression levels of pyroptosis related molecules (NLRP3, GSDMD, caspase1, IL‐1β and IL‐18) gradually increased. It revealed the novel tissues indicators during pyroptosis of HBV liver inflammatory cascade.